A global community-based approach to supporting social and emotional learning - Jae H. Paik; Shinchieh Duh; Rita Rodriguez; Won Kyung Sung; Ji Young Ha; Lisa Wilken; Jong Tak Lee (Social and Emotional Learning: Research, Practice, and Policy)
The benefits of social and emotional learning (SEL) are well-documented in the literature, leading to increased advocacy in school settings. In fact, it has been suggested that SEL should be integrated into all aspects of the students’ life–in every classroom, after-school activity, summer program, and beyond. Therefore, contemporary SEL programming must be flexible to meet the specific needs of the school community and be accomplished with diverse resources without imposing additional burdens on educators or schools. Furthermore, a global perspective is essential, with joint ventures among international educational communities to share teaching approaches, cultural values, and resources. We argue for the necessity of a global community-based approach to create a flexible SEL delivery model. We present two distinct SEL programs, bringing multiple international institutions together to provide enriching learning experiences for all. Through continuous communication and feedback gathered from community members, each SEL program focuses directly on what matters and what is needed for each school community at the time of the collaboration. Actively involving all relevant groups (e.g., students, educators, parents, school districts, university faculty, undergraduates, and pre-service teachers), we demonstrate how a global community-based approach can be applied to bring SEL into mainstream educational practice across the world.